Electrochemical aptasensor array for multiple detection of human osteopontin - Meirinho, S. (2018)
Electrochemical aptasensor arrays have been recently used to detect several proteins reported as disease biomarkers, mainly due to their known advantages, that include high affinity, sensitivity, specificity and low costs, among others. This study describes the development of a label-free electrochemical multi-aptasensor array, for the simultaneous detection of human osteopontin (OPN), using two specific aptamers. To enable multiplexed protein assay, RNA and DNA aptamers were immobilized in the dual-screen-printed gold working electrodes via streptavidin-biotin interaction, and using the [Fe(CN)6]3-/4- as the redox probe for cyclic voltammetry measurements. The multi-aptasensor array herein developed exhibited a good response and selectivity to detect human OPN in the presence of other interfering proteins. Considering these preliminary results, the DNA/RNA dual aptasensor array could potentially be used as an analytical tool for the specific detection of human OPN, and for cancer diagnosis overall. Â© 2018, Sociedade Portuguesa de Electroquimica.